INVESTIGATION OF MICROSTRUCTURE OF STEEL WIRE FOR METAL CORD AND RVD AFTER PATENTING IN CONDITIONS OF RUP «BMZ» - T. P. Kurenkova; E. S. Seregina; A. Ju. Borisenko (Литьë и металлургия, 2009)
The change of microstructure, quantity, character of bainite allocation at lowering of the lead melt temperature is revealed as a result of investigations of microstructure of the samples of steel 80K after isothermal breakdown of austenite in temperature range 610–400 °C.